Virtual water: a helpful perspective, but not a sufficient policy criterion - Wichelns, Dennis (2010)
The topic of virtual water has received substantial attention in recent years, both in scholarly literature and the popular press. Many authors have described the "flow of virtual water? between countries that engage in the trade of agricultural crops and livestock products. Some have suggested that water-short countries should import water-intensive agricultural products from water-abundant countries, while using their limited domestic water resources for higher valued activities. While compelling at first, such a policy prescription can be misleading. Virtual water is a helpful phrase for describing the water required to produce agricultural products and other goods. Discussions of virtual water have been effective in encouraging public officials and citizens to focus on water scarcity issues. Yet the phrase is not based on an underlying conceptual framework. Hence, the virtual water perspective cannot be used alone as a criterion for selecting optimal policies. Trading strategies based on the virtual water perspective are not consistent with the economic concept of comparative advantage. In a similar fashion, distinguishing between the "blue water? and "green water? components of virtual water is helpful in a descriptive sense, but these phrases are not based on an underlying conceptual framework that can serve as a policy criterion for selecting among alternative policy options.